Oral health status of dementia patients in Chiang Mai neurological hospital - Srisilapanan P. (2014)
Objective: Investigate the oral health of patients with dementia and examine the association between the type and severity level of dementia on their dental caries status. Material and Method: Cross-sectional study conducted on outpatients referred to the memory clinic. Clinical examinations were based on WHO criteria. Socio-demographic data, functional ability, and dementia level were obtained from hospital medical records. The Thai version of the Mini Mental State Examination (MMSE-Thai 2002) was used as a cognitive testing instrument. The ability to perform oral care derived from an interview. Results: Sixty-nine subjects were included in the present study. The mean age was 75.5 (±7.0) years. Patients with Alzheimer's disease (AD) constituted the largest dementia group. More than half (60.9%), had dementia for less than two years and were functionally independent (66.7%). The majority (56.5%) had moderately severe dementia. More than half (52.5%) had at least 20 functional teeth. The mean number of teeth was 19.5 (±8.4). Mean decayed, missing, and filled teeth (DMFT) were 14.9 (±9.2). More than half (54.7%) had periodontal disease (pocket depth ≥4 mm). Dementia severity was the only characteristic which showed a significant difference in dental caries experience (p = 0.009). Conclusion: Dementia patients who attended the memory clinic had considerably better oral status compared to the national data. Dementia severity was the only characteristic that showed a significant difference in dental caries experience (p = 0.009). Conclusion: Dementia patients who attended the memory clinic had considerably better oral status compared to the national data. Dementia severity was the only characteristic that showed a significant difference in dental caries experience.